Statistics Workbook For Dummies with Online Practice, 2nd Edition - Rumsey, Deborah (For Dummies, 2019)
Practice your way to a higher statistics score The adage that "practice makes perfect" is never truer than with math problems. S tatistics Workbook For Dummies with Online Practice provides succinct content reviews for every topic, with plenty of examples and practice problems for each concept, in the book and online. Every lesson begins with a concept review, followed by a few example problems and plenty of practice problems. There's a step-by-step solution for every problem, with tips and tricks to help with comprehension and retention. New for this edition, free online practice quizzes for each chapter provide extra opportunities to test your knowledge and understanding. Get FREE access to chapter quizzes in an online test bank Work along with each chapter or use the test bank for final exam review Discover which statistical measures are most meaningful Scoring high in your Statistics class has never been easier!